J-Selaras: New Algorithm for Automated Data Integration Tools - Man, Mustafa; Bakar, Wan Aezwani Wan Abu; Yusof, Mohd. Kamir; Ghani, Norisah Abdul; Arshad, Mohd Adza; Ayob, Raja Normawati Raja; Mahmood, Kamarul Azhar; Ariffin, Faizul Azwan; Kadir, Mohamad Dizi Che; Rosli, Lily Mariya; Yaziz, Nurhafiza Binti Abu (International journal of advanced computer science & applications, 2022)
Data integration is a popular technique or method today for data converting and sharing within new application with different database format and location. The interaction of data from one application system to another application system requires an intermediary software or middleware that allows the data to be transferred or read systematically and easily. The development of dynamic algorithms allows data in various formats, whether structured or unstructured, to be transferred to various types of databases smoothly. A case study was conducted for the Bill of Quantity (BQ) data in the known Excel format generated through CostX software in a single sheet Excel file. It was transferred to a single workbook with multiple sheets with formulation generated automatically. Thus, an algorithm was developed and tested through the development of the J-Selaras System. This algorithm can remove the noisy data or data symbols that are not related in the excel single sheet (CostX) file and automatically transfer to multiple excel sheets with macros formulation quickly. The implementation results indicate a significant contribution where it reduces in execution time of BQ processes and manpower resources used.